Superfine cement-based composite cementing material for underground mine filling and preparation method of superfine cement-based composite cementing material

By adding modified desulfurization gypsum and modified resin to the ultrafine cement-based composite cementing material, a three-dimensional network and interface mask structure was formed, which solved the problems of insufficient strength, high shrinkage rate and poor waterproof performance in the early stage, and achieved high strength and low strength Shrinkage and good waterproofing performance meet the diverse needs of mine filling.

CN119241193AActive Publication Date: 2025-01-03HAINA MEITENG INTELLIGENT MFG (SHANDONG) CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411396273.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-03
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

The problems of insufficient strength, high shrinkage and poor waterproofing performance in the early stage of existing ultrafine cement-based composite cementing materials affect the safety and long-term stability of mine filling.

Method used

Using ultrafine cement, tailings sand, modified desulfurization gypsum, fly ash, modified resin, reinforcement, water reducing agent and fiber material, the three-dimensional network structure is formed through the interaction between modified desulfurization gypsum and modified resin. Interface mask structure improves mechanical strength and waterproof performance and reduces shrinkage.

Benefits of technology

It achieves high strength, low shrinkage and good waterproofing performance, meets the diversity needs of mine filling materials and expands the application environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005073840470000131
    Figure BDA0005073840470000131
  • Figure BDA0005073840470000141
    Figure BDA0005073840470000141
Patent Text Reader

Abstract

The invention relates to the field of cementing materials, in particular to a superfine cement-based composite cementing material for underground mine filling and a preparation method of the superfine cement-based composite cementing material. The superfine cement-based composite cementing material for underground mine filling comprises the following raw materials in parts by mass: 50-70 parts of superfine cement, 20-30 parts of tailing sand, 10-15 parts of modified desulfurized gypsum, 5-12 parts of fly ash, 8-16 parts of modified resin, 0.5-1.5 parts of a reinforcing agent, 0.4-1.2 parts of a water reducing agent, 5-15 parts of a fiber material and 40-60 parts of water. The superfine cement-based composite cementing material prepared by the invention not only has excellent mechanical strength and relatively low shrinkage rate, but also can ensure good water resistance and permeability resistance, so that the diversity performance requirements of the existing mining industry on mine filling materials are effectively met, the application environment of the superfine cement-based composite cementing material is expanded, and the application prospect is wide. And the method has a very excellent application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of cementitious materials, and in particular to an ultrafine cement-based composite cementitious material for underground mine filling and a preparation method thereof. Background Art

[0002] With the development of the mining industry, mine filling technology has become one of the important means to solve the ground pressure control and environmental protection of underground goaf areas. Traditional filling materials are mostly made of a mixture of ordinary cement and tailings. Although they can meet the filling needs to a certain extent, they have problems such as low early strength, large shrinkage, and high cost. In recent years, in order to overcome these problems, researchers have begun to explore the use of ultrafine cement-based composite binder materials. This type of material mixes ultrafine cement with other auxiliary materials (such as slag powder, steel slag, industrial by-product gypsum, etc.), which not only improves the early strength and stability of the filling body, but also effectively reduces the material cost.

[0003] Although the performance of ultrafine cement-based composite binder materials has been improved, the existing technology still faces the following problems: for example, the problem of insufficient early strength. Under certain geological conditions, the filling body needs to quickly reach a certain strength to ensure the safe production of the mine, and the existing ultrafine cement-based composite binder materials still need to be improved in terms of early strength; the shrinkage rate is high, and the filling body is prone to shrinkage cracks during the hardening process, affecting its long-term stability and service life; the waterproof performance is poor, and cracks, breakage and water seepage are prone to occur in a long-term humid environment.

[0004] Therefore, in order to effectively solve the above problems, the present application provides an ultrafine cement-based composite cementing material for underground mine filling and a preparation method thereof. The ultrafine cement-based composite cementing material prepared in the present application not only has excellent mechanical strength and low shrinkage, but also can ensure good water-proof and permeability-resistant performance, thereby effectively meeting the existing mining industry's diverse performance requirements for mine filling materials, expanding the application environment of ultrafine cement-based composite cementing materials, and having very excellent application prospects. Summary of the invention

[0005] In order to solve the above problems, the first aspect of the present application provides an ultrafine cement-based composite binder material for underground mine filling. The raw materials, calculated by mass, are: 50 to 70 parts of ultrafine cement, 20 to 30 parts of tailings sand, 10 to 15 parts of modified desulfurized gypsum, 5 to 12 parts of fly ash, 8 to 16 parts of modified resin, 0.5 to 1.5 parts of reinforcing agent, 0.4 to 1.2 parts of water reducer, 5 to 15 parts of fiber material, and 40 to 60 parts of water.

[0006] As a preferred solution, the mass ratio of the ultrafine cement, tailings sand, fly ash and fiber material is (55-65): (22-26): (8-12): (6-12).

[0007] As a preferred solution, the mass ratio of the ultrafine cement, tailings sand, fly ash and fiber material is (58-64): (24-25): (8-10): (6-8).

[0008] As a preferred solution, the mass ratio of the ultrafine cement, modified desulfurized gypsum and modified resin is (55-65): (11-14): (10-15).

[0009] As a preferred solution, the mass ratio of the ultrafine cement, modified desulfurized gypsum and modified resin is (58-64): (12-13): (12-14).

[0010] As a preferred solution, the average particle size of the ultrafine cement is 5 to 15 μm.

[0011] As a preferred solution, the average particle size of the ultrafine cement is 6 to 10 μm.

[0012] As a preferred solution, the average particle size of the tailings sand is 0.5-1.5 mm.

[0013] As a preferred solution, the average particle size of the tailings sand is 0.8-1.2 mm.

[0014] As a preferred solution, the fly ash is Class I fly ash or Class II fly ash.

[0015] As a preferred solution, the preparation method of the modified desulfurized gypsum includes the following steps: S1: adding desulfurized gypsum to deionized water, adding titanate coupling agent and polyvinyl alcohol and stirring to mix evenly; S2: adding ammonia water, amylopectin and silica sol to the reaction solution, heating to 70-75°C, and keeping the temperature for reaction for 2-2.5 hours; S3: after the reaction is completed, adding urea to the reaction solution, and stirring continuously for 100-120 minutes; S4: after the stirring is completed, filtering the product and placing it in a ventilated oven for drying and keeping the temperature at 80-90°C for 2-3 hours, and the product is obtained after completion.

[0016] As a preferred solution, the mass ratio of the desulfurized gypsum, titanate coupling agent and polyvinyl alcohol is (8-10): (0.5-1): (1.6-2.2).

[0017] As a preferred solution, the mass ratio of the desulfurized gypsum, amylopectin and silica sol is (8-10): (1-1.4): (0.5-0.8).

[0018] As a preferred solution, the amount of urea added is 2.5-5wt% of the total mass of the reaction solution.

[0019] In this application, by adopting the addition of the above-mentioned modified desulfurized gypsum, the mechanical strength of the composite cementing material can be effectively improved and the shrinkage rate can be reduced, and its good waterproof performance can also be effectively maintained. The added modified desulfurized gypsum can form an active coating layer in the system through the surface action of amylopectin and silica sol on the surface of the gypsum particles. The existence of the coating layer can further strengthen the connection inside the cementing material through the surface active groups, especially the interaction with the modified resin can form an internal stable three-dimensional network structure through the multi-branch connection of amylopectin when the composite cementing material is solidified, thereby greatly enhancing the tightness between ultrafine cement particles, and then greatly improving the barrier effect of the composite cementing material for water molecules, thereby reducing the penetration of water molecules in a humid environment, and the formed three-dimensional network structure can strengthen the stability of solid particles in the cementing material, thereby playing an excellent supporting effect, and can play a good impedance during shrinkage, thereby ensuring the various properties of the composite cementing material.

[0020] As a preferred solution, the preparation method of the modified resin comprises the following steps: S1: adding acrylonitrile, glycidyl acrylate and methyl methacrylate to an acryloyl chloride solution, introducing nitrogen, adding potassium persulfate, heating to 80-90°C for reaction to generate a prepolymer; S2: mixing the prepolymer, acrylamide, deionized water and potassium persulfate, fully replacing the reaction system gas with nitrogen, reacting for 6-8h to obtain a modified product solution; S3: adding ammonia water to the modified product solution to adjust the pH to 8-8.5, and naturally cooling, then adding acetone for cyclic washing 2-3 times, and drying to obtain the product.

[0021] As a preferred solution, the mass ratio of acrylonitrile, glycidyl acrylate and methyl methacrylate is (6-8):(1-1.5):(2-3).

[0022] As a preferred solution, the mass ratio of the prepolymer to acrylamide is (10-15):(35-40).

[0023] The above-mentioned modified resin added in the present application can assist in forming a good interface film structure inside the composite adhesive material. The existence of this structure can effectively form an isolation force for water molecules inside the composite adhesive material, thereby greatly reducing the penetration and free speed of water molecules. The existence of the interface film can limit the excessive freeness and shrinkage of particles inside the adhesive material to a certain extent, forming a certain supporting force, thereby improving the overall stability of the internal system of the adhesive material, and can provide better and stable strength during use.

[0024] As a preferred solution, the enhancer is a combination of triethanolamine and calcium chloride.

[0025] As a preferred solution, the mass ratio of triethanolamine to calcium chloride is (1.5-2):(2.5-3.5).

[0026] As a preferred solution, the water reducer is at least one of polycarboxylic acid water reducers.

[0027] As a preferred solution, the fiber material is at least one of carbon fiber, glass fiber, polypropylene fiber, nylon fiber and stainless steel fiber.

[0028] As a preferred solution, the fiber material is glass fiber.

[0029] As a preferred solution, the glass fibers are chopped fibers with an average diameter of 10 to 15 μm and an average length of 6 to 12 mm.

[0030] The second aspect of the present application provides a method for preparing the above-mentioned ultrafine cement-based composite binder material for underground mine filling, which specifically includes the following steps: S1: After weighing the ultrafine cement, tailings sand, modified desulfurized gypsum, fly ash and modified resin in proportion, add them into a mixer for dry mixing, the mixing time is 3 to 5 minutes, and ensure that the components are evenly distributed to obtain a dry mixture; S2: Mix the reinforcing agent, water reducing agent, fiber material and water to obtain a mixed solution, mix the dry mixture and the mixed solution until the slurry is uniform and free of lumps; S3: Fill and cure the obtained slurry, the curing time is 28 days, and the product is obtained after completion.

[0031] The beneficial effects of this application are:

[0032] 1. The ultrafine cement-based composite binder material for underground mine filling provided in the present application not only has excellent mechanical strength and low shrinkage rate, but also can ensure good water penetration resistance, thereby effectively meeting the existing mining industry's diverse performance requirements for mine filling materials, expanding the application environment of ultrafine cement-based composite binder materials, and having very excellent application prospects.

[0033] 2. The addition of modified desulfurized gypsum to an ultrafine cement-based composite binder for underground mine filling provided in the present application can effectively improve the mechanical strength of the composite binder and reduce the shrinkage rate, and can also effectively maintain its good waterproof performance. The added modified desulfurized gypsum can form an active coating layer in the system through the surface action of amylopectin and silica sol on the surface of gypsum particles. The presence of the coating layer can further strengthen the connection inside the binder through the action of the active groups on the surface, especially the interaction with the modified resin can form an internal stable three-dimensional network structure through the multi-branch connection of amylopectin when the composite binder is cured, thereby greatly enhancing the tightness between ultrafine cement particles, and then greatly improving the barrier effect of the composite binder on water molecules, thereby reducing the penetration of water molecules in a humid environment, thereby obtaining good waterproof, anti-shrinkage and strength properties.

[0034] 3. The present application provides an ultrafine cement-based composite binder material for underground mine filling. The modified resin added thereto can assist in forming a good interface film structure inside the composite binder material. The existence of this structure can effectively form an isolation force for water molecules inside the composite binder material, thereby greatly reducing the penetration and free speed of water molecules. The existence of the interface film can limit the excessive freeness and shrinkage of particles inside the binder material to a certain extent, forming a certain supporting force, thereby improving the overall stability of the internal system of the binder material and providing better and more stable strength during use. DETAILED DESCRIPTION

[0035] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.

[0036] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.

[0037] Example 1

[0038] Example 1 The first aspect provides an ultrafine cement-based composite binder material for underground mine filling. The raw materials, calculated by mass, are: 62 parts of ultrafine cement, 24.5 parts of tailings sand, 12.5 parts of modified desulfurized gypsum, 9.5 parts of fly ash, 14 parts of modified resin, 1.2 parts of reinforcing agent, 0.5 parts of water reducer, 7.5 parts of fiber material, and 50 parts of water.

[0039] The average particle size of the ultrafine cement is 8.5 μm, and the product with the corresponding particle size was purchased from Shanghai Kehong New Building Materials Co., Ltd.

[0040] The average particle size of tailings sand is 0.8 mm.

[0041] The fly ash is Class I fly ash.

[0042] The preparation method of modified desulfurized gypsum includes the following steps: S1: adding 9.6 parts of desulfurized gypsum to 180 parts of deionized water, adding 0.8 parts of isopropyl triisostearyl titanate and 1.8 parts of polyvinyl alcohol and stirring to mix evenly; S2: adding 1 part of ammonia water, 1.3 parts of amylopectin and 0.6 parts of silica sol to the reaction solution, heating to 72°C, and keeping the temperature for reaction for 2 hours; S3: after the reaction is completed, adding urea (3.5wt% of the total mass of the reaction solution) to the reaction solution, and stirring continuously for 110 minutes; S4: after the stirring is completed, filtering the product and placing it in a ventilated oven for drying and keeping the temperature at 85°C for 3 hours, and obtaining the product after completion.

[0043] The desulfurized gypsum was purchased from the industrial-grade desulfurized gypsum products sold by Beijing Yiwei New Materials Technology Co., Ltd.

[0044] The polyvinyl alcohol is PVA2488.

[0045] Amylopectin was purchased from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd., and its branched content was ≥75%.

[0046] Silica sol was purchased from Sichuan Muir Chemical Technology Co., Ltd., which sells industrial-grade silica sol products.

[0047] The preparation method of the modified resin comprises the following steps: S1: adding 7.5 parts of acrylonitrile, 1.2 parts of glycidyl acrylate and 2.5 parts of methyl methacrylate to 60 parts of acryloyl chloride solution, introducing nitrogen, adding 0.12 parts of potassium persulfate, heating to 85°C for reaction to generate a prepolymer; S2: mixing 12.5 parts of the prepolymer, 38.5 parts of acrylamide, 200 parts of deionized water and 0.22 parts of potassium persulfate, fully replacing the reaction system gas with nitrogen, reacting for 7.5 hours to obtain a modified product solution; S3: adding ammonia water to the modified product solution to adjust the pH to 8.5, and cooling naturally, then adding acetone for cyclic washing 3 times, and drying to obtain the product.

[0048] The enhancer is a composition of triethanolamine and calcium chloride, and the mass ratio of the two is 1.8:3.

[0049] The water reducer is a polycarboxylate water reducer, which is a high-performance polycarboxylate water reducer purchased from Jinan Yanglan New Material Technology Co., Ltd., and has a water reduction rate of 40%.

[0050] The fiber material is chopped glass fiber with an average diameter of 12 μm and an average length of 8 mm, which is purchased from Wanqing Chemical Technology Co., Ltd.

[0051] The second aspect of the present embodiment provides a method for preparing the above-mentioned ultrafine cement-based composite binder material for underground mine filling, which specifically includes the following steps: S1: After weighing the ultrafine cement, tailings sand, modified desulfurized gypsum, fly ash and modified resin in proportion, add them into a mixer for dry mixing, the mixing time is 4 minutes, and the components are ensured to be evenly distributed to obtain a dry mixture; S2: The reinforcing agent, water reducing agent, fiber material and water are mixed and stirred to obtain a mixed solution, and the dry mixture and the mixed solution are mixed and stirred until the slurry is uniform and free of lumps; S3: The obtained slurry is filled and cured for 28 days, and the product is obtained after completion.

[0052] Example 2

[0053] Example 2 The first aspect provides an ultrafine cement-based composite binder material for underground mine filling. The raw materials, calculated by mass, are: 56 parts of ultrafine cement, 26 parts of tailings sand, 14 parts of modified desulfurized gypsum, 8 parts of fly ash, 10 parts of modified resin, 1.2 parts of reinforcing agent, 0.5 parts of water reducer, 11 parts of fiber material, and 50 parts of water.

[0054] The average particle size of the ultrafine cement is 8.5 μm, and the product with the corresponding particle size was purchased from Shanghai Kehong New Building Materials Co., Ltd.

[0055] The average particle size of tailings sand is 0.8 mm.

[0056] The fly ash is Class I fly ash.

[0057] The preparation method of modified desulfurized gypsum includes the following steps: S1: adding 9.6 parts of desulfurized gypsum to 180 parts of deionized water, adding 0.8 parts of isopropyl triisostearyl titanate and 1.8 parts of polyvinyl alcohol and stirring to mix evenly; S2: adding 1 part of ammonia water, 1.3 parts of amylopectin and 0.6 parts of silica sol to the reaction solution, heating to 72°C, and keeping the temperature for reaction for 2 hours; S3: after the reaction is completed, adding urea (3.5wt% of the total mass of the reaction solution) to the reaction solution, and stirring continuously for 110 minutes; S4: after the stirring is completed, filtering the product and placing it in a ventilated oven for drying and keeping the temperature at 85°C for 3 hours, and obtaining the product after completion.

[0058] The desulfurized gypsum was purchased from the industrial-grade desulfurized gypsum products sold by Beijing Yiwei New Materials Technology Co., Ltd.

[0059] The polyvinyl alcohol is PVA2488.

[0060] Amylopectin was purchased from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd., and its branched content was ≥75%.

[0061] Silica sol was purchased from Sichuan Muir Chemical Technology Co., Ltd., which sells industrial-grade silica sol products.

[0062] The preparation method of the modified resin comprises the following steps: S1: adding 7.5 parts of acrylonitrile, 1.2 parts of glycidyl acrylate and 2.5 parts of methyl methacrylate to 60 parts of acryloyl chloride solution, introducing nitrogen, adding 0.12 parts of potassium persulfate, heating to 85°C for reaction to generate a prepolymer; S2: mixing 12.5 parts of the prepolymer, 38.5 parts of acrylamide, 200 parts of deionized water and 0.22 parts of potassium persulfate, fully replacing the reaction system gas with nitrogen, reacting for 7.5 hours to obtain a modified product solution; S3: adding ammonia water to the modified product solution to adjust the pH to 8.5, and cooling naturally, then adding acetone for cyclic washing 3 times, and drying to obtain the product.

[0063] The enhancer is a composition of triethanolamine and calcium chloride, and the mass ratio of the two is 1.8:3.

[0064] The water reducer is a polycarboxylate water reducer, which is a high-performance polycarboxylate water reducer purchased from Jinan Yanglan New Material Technology Co., Ltd., and has a water reduction rate of 40%.

[0065] The fiber material is chopped glass fiber with an average diameter of 12 μm and an average length of 8 mm, which is purchased from Wanqing Chemical Technology Co., Ltd.

[0066] The second aspect of the present embodiment provides a method for preparing the above-mentioned ultrafine cement-based composite binder material for underground mine filling, which specifically includes the following steps: S1: After weighing the ultrafine cement, tailings sand, modified desulfurized gypsum, fly ash and modified resin in proportion, add them into a mixer for dry mixing, the mixing time is 4 minutes, and the components are ensured to be evenly distributed to obtain a dry mixture; S2: The reinforcing agent, water reducing agent, fiber material and water are mixed and stirred to obtain a mixed solution, and the dry mixture and the mixed solution are mixed and stirred until the slurry is uniform and free of lumps; S3: The obtained slurry is filled and cured for 28 days, and the product is obtained after completion.

[0067] Comparative Example 1

[0068] The specific implementation method of this comparative example is basically the same as that of Example 1, except that the raw materials of the ultrafine cement-based composite binder material used for underground mine filling, in parts by mass, are: 80 parts of ultrafine cement, 20 parts of tailings sand, 6.5 parts of modified desulfurized gypsum, 9.5 parts of fly ash, 22 parts of modified resin, 1.2 parts of reinforcing agent, 0.5 parts of water reducer, 7.5 parts of fiber material, and 50 parts of water.

[0069] Comparative Example 2

[0070] The specific implementation method of this comparative example is basically the same as that of Example 1, except that the raw materials of the ultrafine cement-based composite binder material used for underground mine filling, in parts by mass, are: 70 parts of ultrafine cement, 24.5 parts of tailings sand, 18.5 parts of modified desulfurized gypsum, 9.5 parts of fly ash, 5.5 parts of modified resin, 1.2 parts of reinforcing agent, 0.5 parts of water reducer, 7.5 parts of fiber material, and 50 parts of water.

[0071] Comparative Example 3

[0072] The specific implementation method of this comparative example is basically the same as that of Example 1, except that: the preparation method of modified desulfurized gypsum comprises the following steps: S1: adding 18.5 parts of desulfurized gypsum to 280 parts of deionized water, adding 0.6 parts of isopropyl triisostearyl titanate and 1.2 parts of polyvinyl alcohol and stirring to mix evenly; S2: adding 2.2 parts of ammonia water, 1.3 parts of amylopectin and 0.6 parts of silica sol to the reaction solution, heating to 72°C, and keeping the temperature for reaction for 2 hours; S3: after the reaction is completed, adding urea (3.5wt% of the total mass of the reaction solution) to the reaction solution, and stirring continuously for 110 minutes; S4: after the stirring is completed, filtering the product and placing it in a ventilated oven for drying at 85°C for 3 hours, and obtaining the product after completion.

[0073] Comparative Example 4

[0074] The specific implementation method of this comparative example is basically the same as that of Example 1, except that: the preparation method of modified desulfurized gypsum comprises the following steps: S1: adding 9.6 parts of desulfurized gypsum to 180 parts of deionized water, adding 0.8 parts of isopropyl triisostearyl titanate and 1.8 parts of polyvinyl alcohol and stirring to mix evenly; S2: adding 1.2 parts of ammonia water, 0.5 parts of amylopectin and 3 parts of silica sol to the reaction solution, heating to 72°C, and keeping the temperature for reaction for 2 hours; S3: after the reaction is completed, adding urea (3.5wt% of the total mass of the reaction solution) to the reaction solution, and stirring continuously for 110 minutes; S4: after the stirring is completed, filtering the product and placing it in a ventilated oven for drying at 85°C for 3 hours, and obtaining the product after completion.

[0075] Comparative Example 5

[0076] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified resin comprises the following steps: S1: adding 12.5 parts of acrylonitrile, 0.5 parts of glycidyl acrylate and 1.2 parts of methyl methacrylate to 60 parts of acryloyl chloride solution, introducing nitrogen, adding 0.12 parts of potassium persulfate, heating to 85°C for reaction to generate a prepolymer; S2: mixing 12.5 parts of prepolymer, 38.5 parts of acrylamide, 200 parts of deionized water and 0.22 parts of potassium persulfate, and reacting for 7.5 hours to obtain a modified product solution after nitrogen fully replaces the reaction system gas; S3: adding ammonia water to the modified product solution to adjust the pH to 8.5, and cooling naturally, then adding acetone for cyclic washing 3 times, and drying to obtain the product.

[0077] Comparative Example 6

[0078] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified resin comprises the following steps: S1: adding 7.5 parts of acrylonitrile, 1.2 parts of glycidyl acrylate and 2.5 parts of methyl methacrylate to 60 parts of acryloyl chloride solution, introducing nitrogen, adding 0.12 parts of potassium persulfate, heating to 85°C for reaction to generate a prepolymer; S2: mixing 5.5 parts of prepolymer, 45.5 parts of acrylamide, 240 parts of deionized water and 0.24 parts of potassium persulfate, and reacting for 7.5 hours to obtain a modified product solution after nitrogen fully replaces the reaction system gas; S3: adding ammonia water to the modified product solution to adjust the pH to 8.5, and cooling naturally, then adding acetone for cyclic washing 3 times, and drying to obtain the product.

[0079] Comparative Example 7

[0080] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified resin comprises the following steps: S1: adding 7.5 parts of ethyl acrylate, 1.2 parts of dodecyl acrylate and 2.5 parts of hydroxyethyl acrylate to 60 parts of acryloyl chloride solution, introducing nitrogen, adding 0.12 parts of potassium persulfate, heating to 85°C for reaction to generate a prepolymer; S2: mixing 12.5 parts of prepolymer, 38.5 parts of acrylamide, 200 parts of deionized water and 0.22 parts of potassium persulfate, and reacting for 7.5 hours to obtain a modified product solution after nitrogen fully replaces the reaction system gas; S3: adding ammonia water to the modified product solution to adjust the pH to 8.5, and cooling naturally, then adding acetone for cyclic washing 3 times, and drying to obtain the product.

[0081] Performance Evaluation

[0082] Anti-penetration pressure: The anti-penetration pressure test was carried out on the cementing materials obtained in the examples and comparative examples with reference to the standard GB / T 50082-2009. The results were expressed as the maximum water-free pressure. The test value was the average value of 10 tests and recorded in Table 1.

[0083] Compressive strength: The mechanical strength of the bonding materials obtained in the embodiments and comparative examples was tested with reference to the standard GB / T 50081-2019, and the test values ​​were taken as the average value of 10 tests and recorded in Table 1.

[0084] Anti-corrosion performance: Referring to JC / T 1011-2006, the 28d expansion rate test was carried out on the bonding materials obtained in the examples and comparative examples. The measured values ​​were taken as the average value of 10 tests and recorded in Table 1.

[0085] Table 1 Performance test results

[0086]

[0087]

[0088] It can be seen from the examples and comparative examples of the present application and the data results in Table 1 that Examples 1 and 2 of the present application have obvious advantages over comparative examples 1 to 7 in terms of strength performance, waterproof performance and anti-shrinkage performance. This is mainly due to the combined effect of the modified gypsum, modified resin and other matching technical solutions specified in the present application. Comparative examples 1 to 7 did not adopt the technical solution specified in the present application, resulting in obvious disadvantages in the above-mentioned performance tests. This further proves the necessity of the technical solution specified in the present application for the technical effect of the present application and solving technical problems.

Claims

1. An ultrafine cement-based composite cementing material for underground mine filling, characterized in that: The raw materials are as follows: 50-70 parts of ultrafine cement, 20-30 parts of tailings sand, 10-15 parts of modified desulfurized gypsum, 5-12 parts of fly ash, 8-16 parts of modified resin, 0.5-1.5 parts of reinforcing agent, 0.4-1.2 parts of water reducing agent, 5-15 parts of fiber material, and 40-60 parts of water. The average particle size of the ultrafine cement is 5 to 15 μm; The average particle size of the tailings sand is 0.5 to 1.5 mm; The fly ash is Class I fly ash or Class II fly ash; Preparation method of modified desulfurized gypsum The following steps are involved: S1: Add desulfurized gypsum to deionized water, add titanate coupling agent and polyvinyl alcohol and stir to mix evenly; S2: Add ammonia water, amylopectin and silica sol to the reaction solution, heat to 70-75°C, and keep warm for 2-2.5 hours; S3: After the reaction is completed, add urea to the reaction solution and continue stirring for 100-120 minutes; S4: After stirring, filter the product and place it in a ventilated oven at 80-90°C for drying and heat preservation for 2-3 hours, and the product is obtained after completion; The mass ratio of the desulfurized gypsum, titanate coupling agent and polyvinyl alcohol is (8-10): (0.5-1): (1.6-2.2); The mass ratio of the desulfurized gypsum, amylopectin and silica sol is (8-10): (1-1.4): (0.5-0.8); The amount of urea added is 2.5-5wt% of the total mass of the reaction solution.

2. The ultrafine cement-based composite binder material for underground mine filling according to claim 1, characterized in that: The mass ratio of the ultrafine cement, tailings sand, fly ash and fiber material is (55-65): (22-26): (8-12): (6-12).

3. The ultrafine cement-based composite cementing material for underground mine filling according to claim 2, characterized in that: The mass ratio of the ultrafine cement, the modified desulfurized gypsum and the modified resin is (55-65): (11-14): (10-15).

4. The ultrafine cement-based composite cementing material for underground mine filling according to claim 3 is characterized in that: The preparation method of the modified resin comprises the following steps: S1: adding acrylonitrile, glycidyl acrylate and methyl methacrylate to an acryloyl chloride solution, introducing nitrogen, adding potassium persulfate, heating to 80-90° C. for reaction to generate a prepolymer; S2: mixing the prepolymer, acrylamide, deionized water and potassium persulfate, fully replacing the reaction system gas with nitrogen, reacting for 6-8 hours to obtain a modified product solution; S3: adding ammonia water to the modified product solution to adjust the pH to 8-8.5, and cooling naturally, then adding acetone for cyclic washing 2-3 times, and drying to obtain the modified product; The mass ratio of acrylonitrile, glycidyl acrylate and methyl methacrylate is (6-8):(1-1.5):(2-3).

5. The ultrafine cement-based composite cementing material for underground mine filling according to claim 4, characterized in that: The mass ratio of the prepolymer to acrylamide is (10-15):(35-40).

6. The ultrafine cement-based composite cementing material for underground mine filling according to claim 5, characterized in that: The enhancer is a combination of triethanolamine and calcium chloride.

7. The ultrafine cement-based composite cementing material for underground mine filling according to claim 6, characterized in that: The mass ratio of triethanolamine to calcium chloride is (1.5-2):(2.5-3.5).

8. The ultrafine cement-based composite cementing material for underground mine filling according to claim 7, characterized in that: The water reducer is at least one of polycarboxylic acid water reducers.

9. The ultrafine cement-based composite cementing material for underground mine filling according to claim 8, characterized in that: The fiber material is at least one of carbon fiber, glass fiber, polypropylene fiber, nylon fiber and stainless steel fiber.

10. A method for preparing an ultrafine cement-based composite binder material for underground mine filling according to any one of claims 1 to 9, characterized in that: The specific steps include: S1: After weighing the ultrafine cement, tailings sand, modified desulfurized gypsum, fly ash and modified resin in proportion, add them into a mixer for dry mixing for 3 to 5 minutes to ensure that the components are evenly distributed to obtain a dry mix; S2: Mix the reinforcing agent, water reducing agent, fiber material and water to obtain a mixed solution, mix the dry mixed material and the mixed solution until the slurry is uniform and free of lumps; S3: Fill and cure the obtained slurry for 28 days, and the slurry is obtained after completion.

Citation Information

Patent Citations

  • Glass fiber reinforced gypsum-based composite material and preparation method thereof

    CN108395194A

  • Cementing powder for iron ore pit backfill and preparation method and application thereof

    CN112047703A

  • Filling cementing material for cemented mine superfine tailings, preparation method of filling cementing material and method for cemented filling of tailings by using filling cementing material

    CN114656236A

  • All-solid-waste-based high-strength mine filling cementing material and preparation method thereof

    CN115784703A

  • Shield construction grouting slurry and preparation method thereof

    CN118724546A